A Rare Case of Thoracic Pyogenic Facet Joint Infection - Tomoyuki Setoue; Jun-ichiro Nakamura (Case Reports in Orthopedics)
Pyogenic facet joint infection is a rare but severe infection. The most common complaint on presentation is pain followed by fever, then neurologic impairment. While the lumbar spine is involved in the vast majority of cases presented in the literature, the case presented here occurred in the thoracic spine. The patient was a 48-year-old immune-competent female who presented with left back pain. Magnetic resonance imaging (MRI) indicated a facet effusion, paraspinal abscess, and epidural abscess in the level of 9th-11th thoracic vertebra. On the 6th day of treatment, she presented a neurological disorder and underwent decompressive laminectomy and surgical debridement. We observed immediate improvement as a result of the surgery.